Pretreatment Lipoprotein(a) as a Biomarker for EGFR Mutation and Prognosis in Lung Adenocarcinoma - Liu J; Liu Z; Xu D; Zhou T; Li A; Hu J; Li H; Li W; Wang Z; Yu Z; Zeng L (International Journal of General Medicine)
Ji Liu,1 Zhekang Liu,2 Deming Xu,1 Tao Zhou,1 Ang Li,1 Jiali Hu,1 Hong Li,3 Wenjie Li,1 Zengqing Wang,1 Zhiping Yu,1 Linxiang Zeng1 1Department of Respiratory and Critical Care Medicine, the Second Affiliated Hospital of Nanchang University, Nanchang, Jiangxi Province, People’s Republic of China; 2Rheumatology and Immunology department, the Second Affiliated Hospital of Nanchang University, Nanchang, Jiangxi Province, People’s Republic of China; 3Department of Geriatrics, the First People’s Hospital of Jiashan County, Jiaxing, Zhejiang Province, People’s Republic of ChinaCorrespondence: Linxiang Zeng, Department of Respiratory and Critical Care Medicine,The Second Affiliated Hospital of Nanchang University, No. 1, Minde Road, Nanchang City, Jiangxi Province, 330006, People’s Republic of China, Email zenglinxiang1972@163.comPurpose: This study aims to investigate the correlation between pretreatment serum lipoprotein(a) [Lp(a)] and epidermal growth factor receptor (EGFR) gene mutations, as well as its predictive value for progression-free survival (PFS) in advanced lung adenocarcinoma patients receiving epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) therapy.Patients and Methods: We determined the optimal cutoff value for Lp(a) by receiver operating characteristic (ROC) curves and Youden’s index to categorize Lp(a) into high and low groups. Logistic regression was used to analyze the EGFR mutation rate in different groups. Additionally, the relationship between pretreatment Lp(a) levels and prognostic PFS in patients with advanced (TNM stage IIIB-IV) lung adenocarcinoma treated with EGFR-TKIs was retrospectively analyzed by Cox regression, survival and stratified analysis methods.Results: We included 338 advanced lung adenocarcinoma patients, with median age of 64 years, and slightly more female patients (51.8%), most of whom had no smoking history (70.7%), no history of chronic lung disease (87.9%), and stage IV (81.1%) patients. The EGFR gene mutation rate was 55.3% and 123 patients were included in the prognostic evaluation through screening. The optimal cutoff value for Lp(a) was 20.48 mg/L. The mutation rate in the high Lp(a) group was significantly lower than the low Lp(a) group (48.0% vs 65.5%, p = 0.001). Multivariate logistic regression analysis indicated that Lp(a) is an independent predictor of EGFR mutations (OR = 0.41, 95% CI: 0.25– 0.66, p< 0.001). Survival analysis showed that the median PFS was significantly longer in the high Lp(a) level group compared to the low level group (16.1 months, 95% CI: 11.9– 23.8 months vs 9.6 months, 95% CI: 8.9– 13.3 months, p=0.015). Multivariate analysis confirmed that Lp(a) is an independent predictor of PFS in advanced lung adenocarcinoma patients receiving EGFR-TKIs treatment (HR = 0.42, 95% CI: 0.26– 0.68, p< 0.001).Conclusion: Pretreatment Lp(a) may be a biomarker for EGFR mutations and the PFS in advanced lung adenocarcinoma patients undergoing EGFR-TKIs treatment.Keywords: advanced lung adenocarcinoma, lipoprotein (a), epidermal growth factor receptor, progression-free survival, Biomarker